ANALYSIS OF TOTAL ORGANIC MATTER AND FITOPLANKTON ABUNDANCE IN THE DUMAI RIVER ESTUARY WATERS OF RIAU PROVINCE - Rasmiati, Eva; Nedi, Syahril; Amin, Bintal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in February to March 2017 in Dumai River estuary of Riau Province, with the aim to find out if there is any differences the total organic matter content and the abundance of phytoplankton between stations, and the relationship between total organic matter with the abundance of phytoplankton. The method used is a survey method consisting of 4 stations with 3 replications at each station. Based on the results, the highest average total organic content was found in Station 1 (24,01 mg/L) and lowest was at Station 3 (7,37 mg/L). There is a difference of total organic matter content between stations. There are 8 types of phytoplankton that found on the surface waters of the Dumai River estuary, where the most dominant type is Isthmia sp. The highest abundance of phytoplankton was found at Station 4 (4443,98 ind/L), and the lowest was at Station 2 (1367,41 ind/L). There was no difference in abundance of phytoplankton between stations. The relationship of total organic matter content with phytoplankton abundance shows a moderate negative relationship, which means that the increasing of total organic matter content will decrease the abundance of phytoplankton in the waters of Dumai River estuary.Keywords: Dumai River Estuary, Abudance of Phytoplankton, Total Organic Matter